Screening for Latent Tuberculosis Infection in Adults: US Preventive Services Task Force Recommendation Statement - Mangione, Carol M; Barry, Michael J; Nicholson, Wanda K; Cabana, Michael; Chelmow, David; Coker, Tumaini Rucker; Davis, Esa M; Donahue, Katrina E; Jaén, Carlos Roberto; Li, Li; Ogedegbe, Gbenga; Rao, Goutham; et al. (JAMA : the journal of the American Medical Association, 2023)
In the US, tuberculosis remains an important preventable disease, including active tuberculosis, which may be infectious, and latent tuberculosis infection (LTBI), which is asymptomatic and not infectious but can later progress to active disease. The precise prevalence rate of LTBI in the US is difficult to determine; however, estimated prevalence is about 5.0%, or up to 13 million persons. Incidence of tuberculosis varies by geography and living accommodations, suggesting an association with social determinants of health. To update its 2016 recommendation, the US Preventive Services Task Force (USPSTF) commissioned a systematic review on LTBI screening and treatment in asymptomatic adults seen in primary care, as well as the accuracy of LTBI screening tests. Asymptomatic adults 18 years or older at increased risk for tuberculosis. The USPSTF concludes with moderate certainty that there is a moderate net benefit in preventing active tuberculosis disease by screening for LTBI in persons at increased risk for tuberculosis infection. The USPSTF recommends screening for LTBI in populations at increased risk. (B recommendation).